Non-genetic factors affecting milk production traits of Sahiwal cattle at organized dairy herd (Indian Journal of Animal Production and Management, 2017)
The study was conducted to evaluate production traits using records of 462 Sahiwal cows, spread over  a period of 15 years (1997-2011), maintained at Livestock Research Centre, National Dairy Research  Institute, Karnal. Data was analyzed by least squares technique to examine the effect of non-genetic  factors on various economic traits in zebu cattle. Overall least squares means of total milk yield (TMY),  milk yield per day lactation length (MY/LL), milk yield per day calving interval (MY/CI) were 1760.62±32.96  kg, 6.34±0.74 kg and 4.40±0.83 kg, respectively. Effect of season of calving was significant (P
Keywords: Milk yield; Non-genetic factors; Sahiwal cattle